Unroofing of Lower Pole Native Kidney Cysts in Patients with Autosomal Dominant Polycystic Kidneys at the Time of Kidney Transplantation - Basiri, Abbas; Simforoosh, Nasser; Nayebzade, Amirhossein; Marufi, Hamed; Kashi, Amir Hossein (Urology Journal, 2023)
To report our experience with unroofing of ipsilateral lower pole kidney cysts in five patients with adult-type polycystic kidneys [ADPKD] when free implantation of kidney allograft interfered with lower pole native kidney cysts. In all of these patients, the native kidneys extended to the ipsilateral pelvis and bilateral ADPKD caused enlargement of the abdomen on gross examination. Unroofing of lower pole kidney cysts was performed during the same session of allograft transplantation. The decision to unroof lower pole cysts of the ipsilateral kidney was made after observing interference of lower pole cysts with free implantation of the allograft. In patient A, bilateral native nephrectomy was performed 6 weeks after kidney transplantation after consultation with the patient, when there was evidence of the good function of the allograft and the recipient was on a low dose of immunosuppressive medications. In other patients, no need for native nephrectomy observed. This experience suggests the possibility that when large ipsilateral kidney cysts interfere with safe implantation of the allograft, there is an option of performing cyst unroofing at the same session and proceeding with allograft implantation. In many patients, there would be no need for native nephrectomy and of deemed necessary, it will be performed later, when there is evidence of the good function of the allograft and the patient is on good kidney function with a low dose of immunosuppressive medications and a less risk profile for the operation. To our best knowledge, there is no prior such report in the literature.